Old Polish warrior's path - psychophysical and martial preparation of a young nobleman in modern Poland - Pokojski, Jakub (Revista de Artes Marciales Asiáticas, 2019)
The article attempts to outline the path a young nobleman underwent in the 16-17th century Poland in order to achieve prowess in battle martial arts. It presents patterns and ways of training the nobleman was subjected to from an early age, the process of a future warrior’s mental and physical preparation. Furthermore, it describes various types of body exercises and trainings with many weapon types. A fundamental novelty is presentation of the training methodology. Its over four centuries of age notwithstanding it has basically been valid until nowadays and encompasses such features as diet or exercise intensity. Eventually this article presents the individual stages of said training, closely related to warrior’s age and psychophysical development. Material for the study was obtained thanks to the textual analysis, both from the era (16 to 17th century sources) and from the limited literature on the topics (monographs, magazine articles, periodicals, the Internet) addressing the subject. The result depicts arduous, however consistent and sensible old Polish training system. After many years of wisely carried out exercises an effective, skilled warrior was produced, furnished with high fighting skills and morale, ready to fight his country enemies. At the same time whilst getting old such a warrior could train the next generations of Homeland’s knights-defenders. The objective of the article is to draw attention to the subject of Polish warriors, their training and martial arts, hitherto unmentioned in English literature and to encourage further research in this field.